Analisis Marketing Mix Syariah Pada Hotel Qieran Syariah Kota Bengkulu - Julianti Julianti; Nurul Hak; Aan Shar (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study was to describe the sharia marketing mix at the qieran sharia hotel in Bengkulu city. This research method is a type of field research (field research) with a qualitative method approach. The results of the study concluded that the marketing mix, namely 7P (product) of the Qieran Syariah Hotel, is known as a hotel that applies sharia principles, besides that the services provided are also good, and also provide comfort and safety for guests who stay there. (Price) Hotel Qieran Syariah in providing prices that are appropriate and affordable, (Place) Hotel Qieran Syariah is based on facts that are in a strategic and affordable location not to disturb the surrounding community, (Promotion) through online media such as Facebook, Instagram, the traveloka application, agoda, pegi-pegi, and tiket.com, as a tool to attract consumers. Hotel Qieran Syariah provides promos through online applications, (People) in selecting HR conduct training so that they welcome guests in a friendly, polite and transparent manner in receiving and serving guests , the disadvantage is that it does not have an organizational structure, this can be seen from the employees who change every month. (Process) especially the facilities, equipment and rooms in the hotel are still functioning properly, (Physical Aviedence) such as decorations and interiors that have implemented the concept of sharia with calligraphy extensions, prayers and asmaul husna at each room door.